Avaliação de indicadores de adaptação à mudanças dietéticas em ruminantes - Farenzena, Roberta (2013)
Two in vivo digestibility assays with sheep were conducted to evaluate the impact of diet changing on nutritional variables, including voluntary intake, digestibility and ruminal fermentation, as well as to stablish the minimum lenght of feeding period as to obtain reproducible values of these variables. Assay 1 was conducted with 10 Polwarth wethers (34 ± 5 kg body weight (BW)), housed in metabolism cages, throughout three 21 d experimental periods, in a completely randomized 2-way crossover design. The animals were divided in two groups (Group A e B, n=5 per group) which were fed ad libitum with a sequence of the following diets throughout the experimental periods: Group A: hay hay+concentrate hay; Goup B: hay+concentrate hay hay+concentrate. It was used a Cynodon sp. hay and a concentrate composited by grain corn, soybean meal and wheat meal, which was included in a proportion of 50% of total diet dry matter. The intake, fecal excretion and digestibility of the organic matter, neutral detergent fibre and N compounds, as well as the urinary excretion of N and alantoin were daily measured throughout the experiment. The Assay 2 was conducted to evaluate some parameters of ruminal fermentation (i.e. pH, in situ degradation, microbial adherence and microbial enzyme activity on residue of in situ incubation). It was used the same experimental design of Assay 1, excepting that it was conducted with four Santa Inês sheep (65 ± 5 kg de BW, n=2 per group), fitted with ruminal cannula, and included one additional 21 d experimental period (i.e total of four 21 d periods, as a 3-way crossover design). Most nutritional variables were impacted by diet changing, and the time of adaptation varied from 6 to 13 days, depending of the variable and diet type. The results of the present study indicate that the minimum adaptation period for in vivo digestibility assays should be of 14 d long.